Insights from healthcare academics on facilitating interprofessional education activities. Issue 5 (3rd September 2021) - El-Awaisi, Alla; Sheikh Ali, Saba; Abu Nada, Aya; Rainkie, Daniel; Awaisu, Ahmed
ABSTRACT: Facilitators are of paramount importance to the success of interprofessional education (IPE) activities; hence, it is crucial to explore their perspectives and experiences in delivering IPE in Qatar. Using an exploratory case study approach, semi-structured interviews were conducted, in 2018, among faculty members, who had facilitated at least one IPE activity in Qatar, from healthcare professional education programs at Qatar University Colleges of Pharmacy, Medicine, and Health Sciences, Weill Cornell Medicine in Qatar, the University of Calgary in Qatar, and the College of North Atlantic. Interviews were recorded and transcribed verbatim. Inductive thematic content analysis was implemented. Twenty-one interviews were conducted with the following professions represented: medicine (n = 6), pharmacy (n = 5), nursing (n = 4), biomedical science (n = 3), respiratory theory (n = 2) and public health (n = 1). Four main themes emerged from the interviews: drivers to facilitator involvement that included interest and commitment to IPE and awareness of collaborative practice benefits; facilitator participation which was based on facilitator attributes and preparedness and readiness for IPE facilitation; the organizational support in terms of dedicated structure for IPE and IPE design and delivery and; student participation in terms of group dynamics and student engagement. Some key recommendations include having a dedicated unit for IPE, scheduling protected time for IPE, and organizing facilitators' training and debriefing workshops. The facilitators valued and appreciated IPE in preparing students for future collaborative practice. These findings can inform the development of quality and sustainable IPE activities in the future.